2016
DOI: 10.1103/physrevlett.116.108701
|View full text |Cite
|
Sign up to set email alerts
|

Congestion Induced by the Structure of Multiplex Networks

Abstract: Multiplex networks are representations of multilayer interconnected complex networks where the nodes are the same at every layer. They turn out to be good abstractions of the intricate connectivity of multimodal transportation networks, among other types of complex systems. One of the most important critical phenomena arising in such networks is the emergence of congestion in transportation flows. Here, we prove analytically that the structure of multiplex networks can induce congestion for flows that otherwis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
89
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 25 publications
1
89
0
1
Order By: Relevance
“…References [34,35] provide more comprehensive reviews of this work. Approaches for detecting communities in multiplex networks are also relevant [36][37][38][39][40][41][42][43][44][45], as dynamic networks are a special case of multiplex networks, in which the layers are organized in a linear sequence. However, despite these varied efforts, up to now we have lacked a theoretical understanding of the optimality of these techniques, when or how they tend to fail, or whether there are fundamental limits to detecting community structure in dynamic networks.…”
Section: Introductionmentioning
confidence: 99%
“…References [34,35] provide more comprehensive reviews of this work. Approaches for detecting communities in multiplex networks are also relevant [36][37][38][39][40][41][42][43][44][45], as dynamic networks are a special case of multiplex networks, in which the layers are organized in a linear sequence. However, despite these varied efforts, up to now we have lacked a theoretical understanding of the optimality of these techniques, when or how they tend to fail, or whether there are fundamental limits to detecting community structure in dynamic networks.…”
Section: Introductionmentioning
confidence: 99%
“…These means that, in two-layer multiplex networks, shortest paths between two nodes may exist in just one layer, in the other layer, in a path with transfers (what we call multiplex paths), or in a combination of them (see figure 1). Consequently, any property depending on paths in multiplex networks must consider the concept of source and destination as being intrinsically different to that of nodes, such as in the calculation of centrality measures [22][23][24], the analysis of interdependence [30], the analysis of random walks [21], or the study of congestion [29]. The former definition of shortest paths in multiplex networks imposes the necessity of correctly computing their distribution and multiplicity.…”
Section: Shortest Paths In Multiplex Networkmentioning
confidence: 99%
“…If the capacity of some nodes to process these elements is lower than their incoming rate, congestion emerges [7]. In the general case of multiplex networks [29], it was shown that congestion appears when the injection rate per node, ρ, reaches a critical value ρ c :…”
Section: Congestion In Multiplex Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8]-and dynamic processes [9], such as mobility on urban multiplexes. The latter-which is the focus of this contribution, see next Section-has been tackled only recently [10][11][12].…”
Section: Introductionmentioning
confidence: 99%